OntoJogo: an ontology for game classification - Teixeira, Salete (2020)
Games are no longer just an entertainment activity. Various games are being adopted in different fields, such as psychology, education, and healthcare. Their usage requires professionals to be capable of categorizing games to take the most advantage out of them. Therefore, we argue that a uniform classification for games can facilitate and improve the work on numerous investigations that focus on the usage of games. Along with research work on the matter, in this paper, we present an ontology, OntoJogo, for the classification of games according to different perspectives or categorization axes. In the paper, OntoJogo is described in detail (classes and relations are explained), and examples of use are shown.